Saccharomyces cerevisiae and Oenococcus oeni immobilized in different layers of a cellulose/starch gel composite for simultaneous alcoholic and malolactic wine fermentations - Servetas, Ioannis; Berbegal, Carmen; Camacho, Nathalia; Bekatorou, Argyro; Ferrer, Sergi; Nigam, Poonam Singh; Drouza, Chryssoula; Koutinas, Αthanasios Α. (My University, 2013)
The production of a two-layer composite biocatalyst for immobilization of two different microorganisms for simultaneous alcoholic and malolactic fermentation (MLF) of wine in the same bioreactor is reported. The biocatalyst consisted of a tubular delignified cellulosic material (DCM) with entrapped Oenococcus oeni cells, covered with starch gel containing the alcohol resistant and cryotolerant strain Saccharomyces cerevisiae AXAZ-1. The biocatalyst was found effective for simultaneous low temperature alcoholic fermentation resulting to conversion of malic acid to lactic acid in 5 days at 10 °C. Improvement of wine quality compared with wine fermented with S. cerevisiae AXAZ-1 immobilized on DCM was attributed to MLF as well as to increased ester formation and lower higher alcohols produced at low fermentation temperatures (10 °C) as shown by GC and headspace SPME GC/MS analysis. Scanning electron microscopy showed that the preparation of a three-layer composite biocatalyst is also possible. The significance of such composite biocatalysts is the feasibility of two or three bioprocesses in the same bioreactor, thus reducing production cost in the food industry.
Keywords: Composite biocatalyst; Immobilization; Malolactic fermentation; Oenococcus oeni; Saccharomyces cerevisiae; Wine